Emerging Techniques in Power System Analysis - Dong, Zhaoyang; Zhang, Pei.; Ma, Jian.; Zhao, Junhua; Ali, Mohsin; Meng, Ke.; Yin, Xia.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
"Emerging Techniques in Power System Analysis" identifies the new challenges facing the power industry following the deregulation. The book presents emerging techniques including data mining, grid computing, probabilistic methods, phasor measurement unit (PMU) and how to apply those techniques to solving the technical challenges. The book is intended for engineers and managers in the power industry, as well as power engineering researchers and graduate students. Zhaoyang Dong is an associate professor at the Department of Electrical Engineering, The Hong Kong Polytechnic University, China. Pei Zhang is program manager at the Electric Power Research Institute (EPRI), USA.
Fundamentals of Emerging Techniques -- Data Mining Techniques and Its Application in Power Industry -- Grid Computing -- Probabilistic vs Deterministic Power System Stability and Reliability Assessment -- Phasor Measurement Unit and Its Application in Modern Power Systems -- Conclusions and Future Trends in Emerging Techniques.
Keywords: Energy systems; Control engineering; Robotics; Mechatronics; Energy Systems; Control, Robotics, Mechatronics; Energy Systems